Taxonomic importance of the prefemoral process of the first pair of legs in males of the genus Pseudonannolene (Diplopoda, Spirostreptida) - Fontanetti, Carmem S. [UNESP] (My University, 2002)
The first pair of legs in males of some groups of diplopods is modified, having a large coxa and oral projecting prefemoral process; in the family Spirostreptidae (Spirostreptida) this structure has relevance on the genus level. This paper discusses the shape, presence, and absence of the prefemoral process in the genus Pseudonannolene (Pseudonannolenidae, Spirostreptida) and suggests that this structure is an important taxonomic character in this genus and can be used for distinguishing some species.
Keywords: Diplopods; Millipedes; Pseudonannolene; Taxonomy; diplopoda; femur; insect; leg; nonhuman; Pseudonannolenidae; species differentiation; species diversity; spirostreptida; taxonomic identification; taxonomy; Animals; Classification; Extremities; Femur; Male; Sex Characteristics; Species Specificity; Diplopoda; Insecta; Spirostreptida; Spirostreptidae